Patterns Of Islamic Education Moderation In Indonesian History - Najib, Abdul (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2018)
This article aims to find out and describe the pattern of Islamic education moderation in Indonesian history. Islam in Indonesia is manhaj tawasuá¹ (moderate). With manhaj, Islam as a religion followed by the majority of the Indonesian population succeeded in entering into every aspect of life in Indonesia from social, cultural, economic and even political and government bureaucracy. Similarly, Islamic education managed to occupy an important position in education in Indonesia. Even though it is an alternative education, the fact is that Islamic education in Indonesia is a very important part to educate the nation. Moderation of Islamic education in Indonesia began with the first education model in Indonesia, namely pesantren. The pattern of moderation found from pesantren is cultural acculturation which is very obvious, from the knowledge learned to educational methods used, Arabic pegon to fill the language gap. The next phase is accommodation patterns that we can see from madrasa that adapts the classical government system from the colonial side. The next pattern is formalization that can be described through the phenomenon of state madrasas. Then, the latest is mu'adalah policy and formal diniyyah education. From these patterns it can be concluded that Indonesian Islamic education always takes the middle way (wasaá¹iyyah) of every challenge that arises due to historical movements. This modernization is a genius manner by paying attention to the rules of muá¸¥afadzah â€˜alÄqadÄ«m al-á¸¥Äliá¸¥ wa al-akhdzu bi jadÄ«d al-aá¹£laá¸¥. With this understanding, Islamic education in Indonesia will always be relevant in every space and time (á¹£aliá¸¥li kull zamÄn wa makÄn) as aspired by the salÄf al-á¹£aliá¸¥.